THE EFFECT OF INFORMATIONAL GAP ACTIVITY TO THE UNMOTIVATED STUDENTS’ ABILITY OF 8th GRADERS AT MTS AL HASANAH 1 SLAHUNG, PONOROGO (RETAIN, 2014)
THE EFFECT OF INFORMATIONAL GAP ACTIVITY TO THE UNMOTIVATED STUDENTS’ ABILITY OF 8th GRADERS AT MTS AL HASANAH 1 SLAHUNG, PONOROGO Diyan Novika English Education Department, Language and Art Faculty, Surabaya State University. ndidy71@gmail.com Drs Fahri, M.A English Education Department, Language and Art Faculty, Surabaya State University. fahri@englishunesa.com Abstract The aims of this research is to find out the improvement of unmotivated students’ speaking ability after treating by using Informational Gap Activity in teaching English of the eight grader of Mts Al Hasanah 1 Slahung Ponorogo. The method that is used in this study is a quantitative method. This design of study had more potential threat to internal validity as the time between pretest and posttest increases and as experimental situation become less controlled and contrived (Mc Millan, 1992 : 175) the design of single group of pretest and posttest. The data on students’ English speaking ability were collected with a performance test. The hypothesis were tested with two-ways analysis using statistic calculation of T-test formula with significance degree 5% and 1%. And the other one is using questionnaire. The results of analysis showed that: (1) there were differences of the English speaking ability between the unmotivated students who learned through and that of the unmotivated students who learned through conventional method The result is 2,045 < 7,389 > 2,756 (2) and the other one is from their responses based on the questionnaire. The conclusion is that the implementation of Informational Gap Activity method has an effect on the English speaking ability viewed from students’ verbal aptitude. Keywords: Unmotivated students, Informational Gap Activity INTRODUCTION English becomes the most essential language in the world. Almost all the people from many different countries around the world use it to communicate. The area of English has always become a special interest. It is spoken by millions of people all over the world. Genc (2007, p. 6) says that "when we learn a language, there are four skills that we need for complete communication. When we learn our native language, we usually learn to listen first, then to speak, then to read, and finally to write. These are called the four “language skills”. As a consequence, English serves for many times many more people as a barrier between themselves and those some fields of interest, many people in their own countries will not be able to become doctors, for example if they cannot learn enough English. That’s some reasons why English is important. Actually, learning process becomes the primary reference for determining success in learning. But, the more we get in our nation nowadays are most teachers do not pay attention and assume that this is not an important thing to discuss. On the contrary, it is very important for our education. According to the 2006 National Study of Junior/Senior High School Student Engagement (Yazzie-Mintz, 2007), two of three high school students are bored every day in class—typically, they say, because the work isn't interesting, challenging, or relevant for them. It seems that the classroom activities didn’t interesting anymore for them. One more thing that we have to know is that the classroom is a social construct that is designed to facilitate learning. While learning can occur even when the only active participant is the student-as is the case when a person is reading a user manual the most effective learning scenarios are those that involve the proactive involvement of both instructors and students. The fundamental benefit of a personal student-teacher type of interaction is that the feedback and control mechanism is firmly established and can always be invoked to maintain the learning direction towards pre-set objectives. Moreover, the learning process is essentially affected by peer-group relationships within the classroom environment. That is, the interactions between teachers and students as well as among students constitute the learning network within which lesson concepts are shared, affirmed, and built upon. When disconnect occurs between teachers and students, the class becomes ineffective. Sutherland and Singh ( 2004 ) said “states that passive learning contributes to the failure of students”. The lack of adequate student involvement almost certainly spells cognitive failure, especially when the opportunities to learn and practice English outside the classroom are rare or isolated. We can imagine what will happen with the student in that condition. Sure, unmotivated student will really increase just because of passive learning. And the more problem frequently found caused from that condition is that because of motivation lack to practice the second language in daily conversation. They are also too shy and afraid to take part in the conversation and afraid to make mistakes. Many factors can cause the problem of the students. Speaking skills here namely the students that learning language. Interest the material and the media among others including the technique in teaching English. Educator in general will agree with the importance of motivation as a key to success in language acquisition as it’s both of condition and a result of effective interaction (winne and mark, 1989) “journal of information management education volume 11, 2012” Now, let’s compare between what Yazzie-Mintz and Genc. Yazzie-Mintz said based on their research that there are two of three high school students are bored every day in class and the typically cause is that the work isn't interesting, challenging, or relevant for them. It seems that the classroom activities didn’t interesting anymore for them. The second is about Genc statement (2007, p. 6) he said "when we learn a language, there are four skills that we need for complete communication. In the other hand, the class activity should be continuing as well as possible to make the student able to speak English, at least they have braveness to speak. Especially for the unmotivated student, and there should be good activities to face them. Of course the methods/activity should be interesting. One of them is by giving students information – gap activity which might make the students interact easily in speaking activity. Sari (2008,p. 3) says, "the core of information gap method is a corporation between groups and pairs". Information gap activities involve the learners in sharing the information that they have in order to solve a problem, gather information or make decisions (Rees,2005, p. 156). So, English language learning students should be involved in as many situations as possible where one of them has some information and another does not, but has to get it. In other words, situations containing an information gap between the participants are very useful. Neu and Reeser (1997, p. 127) said that in an information gap activity, one person has certain information that must be shared with others in order to solve a problem, gather information or make decisions. Information gap is a useful activity in which one person has information that the other lacks. Another advantage of information gap activities is that students are forced to negotiate meaning because they must make what they are saying comprehensible to others in order to accomplish the task (Neu and Reeser, 1997, p. 128). For these reasons, the writer is interested in analyzing the effect of Information Gap Activity to the unmotivated students’ speaking ability of 8th graders at Mts Alhasanah 1 Slahung, Ponorogo METODE This section presented the steps how the researcher conducts the study. It covers the research design, participant of study, research instrument, procedure of collecting data, and data analysis. This research was an experimental research. It was done to find out the effect of Information Gap Activity to teach the unmotivated students speaking ability of the eight graders junior high student of Mts Al-Hasanah 1 Slahung. The method that is used in this study is a quantitative method. The study is based on both library and a field research. In the field research, the writer collected the data by using observing teaching and also treat the student (teaching English using information gap activity) learning the subjects. In this study, the researcher just used one group an experimental group. It is called as single group pretest-posttest design. And the results were determined by comparing the pretest and posttest scores. This design of study had more potential threat to internal validity as the time between pretest and posttest increases and as experimental situation become less controlled and contrived (Mc Millan, 1992 : 175) the design of single group of pretest and posttest is presented below: Table 2 Single group pretest and posttest design Group Pretest Treatment Posttest A Y1 X Y2 In which: A : The group of subjects Y1 : The pre-test given before treatment X : The independent variable or treatment where information gap activity was applied Y2 : The post-test given before treatment There were two variables in this study. There were dependent variable and independent variable. In this case, the independent variable is the teaching technique “informational gap activity”. And the dependent variable would be the students’ speaking ability. Based on (Mc Millan, 1992:22) stated that independent variable is the first thing that influence or predict the result. As the dependent variable is the students’ speaking score. According to Mc Millan (1992:22), dependent variable is something that affected and predicted by the independent variable. The Participants of the study is ninth graders of mts Al Hasanah 1 Slahung, Ponorogo. It is located at Jalan Ponorogo-Pacitan. The researcher chose the place because the researcher graduated from there so that it makes the researcher easier to conduct the research there. There is one instruments use by the researcher in his study. There is: speaking performance (which is the score of pronunciation, grammar, vocabulary, fluency and comprehension) that would be applied using pre-test and post-test. The data from the score of speaking performance test are collected from two tests which are pre-test and post-test. And the data is presented in quantitative manner since the study is experimental research. These tests are to find out the unmotivated students’ speaking ability. Before implementing the technique, the researcher teaches them without using Information Gap Activity. Then the researcher administered pre-test to the students. The students are asked to perform their speaking in front of the class with their friend then the researcher asked the some question about the materials about telling the time. In the next day the researcher gives them two times treatment or teaching speaking using Information Gap Activity then he gives the post-test to know the result by using rubric of speaking as below: a. Accent Pronunciation frequently unintelligible. Frequent gross errors and a very heavy accent make understanding difficult, require frequent repetition. “Foreign accent” requires concentrated listening and mispronunciation lead to occasional misunderstanding and apparent errors in grammar or vocabulary. Marked “foreign accent” and occasional mispronunciations which do not interfere with understanding. No conspicuous mispronunciations, but would not be taken for a native speaker. Native pronunciation, which no trace of “foreign accent”. b. Grammar Grammar almost entirely inaccurate except in stock phrases. Constant errors showing control of very few major patterns and frequently preventing communication. Frequent errors showing some major patterns uncontrolled and causing occasional irritation and misunderstanding. Occasional errors showing imperfect control of some patterns but no weakness that causing misunderstanding. Few errors, with no patterns of failure. No more than two errors during the interview. c. Vocabulary Vocabulary inadequate for even the simplest conversation. Vocabulary limited to basic personal and survival areas (time, food, transportation, family, etc.) Choice of words sometimes inaccurate, limitation of vocabulary prevent discussion of some common professional and social topics Professional vocabulary adequate to discuss special interest; general vocabulary permits discussion of any non-technical subject with some circumlocutions. Professional vocabulary broad and precise; general vocabulary adequate to cope with complex practical problems and varied social situation. Vocabulary apparently as accurate and extensive as that of an educated native speaker d. Fluency Speech is so halting and fragmentary that conversation is virtually impossible. Speech is very slowly and uneven except for short or routine sentences. Speech is frequently hesitant and jerky; sentences may be left uncompleted. Speech is occasionally hesitant, with some unevenness caused by rephrasing and grouping for words. Speech is effortless and smooth, but perceptibly non-native in speed and evenness. Speech is on all professional and general topics as effortless and smooth as a native speaker’s. e. Comprehension Understanding only slow, very simple speech on common social and touristic topic; requires constant repetition and rephrasing. Understanding little for the simplest type of conversation. Understanding careful, somewhat simplified speech directed to him, with considerable repetition and rephrasing. Understands quite well normal educated speech directed to him, but requires occasional repetition and rephrasing. Understands everything in normal educated conversation except for every colloquial or low-frequency items, or exceptionally rapid or slurred speech. Understands everything in both formal and colloquial speech to be expected of an educated native speaker. To know the result of teaching speaking by using Information Gap Activity, the writer gives oral test to the students. Because the test is oral test, the writer divided the score into five criteria, which are the scores of pronunciation, grammar, vocabulary, fluency and comprehension. Then, the data from pre-test, they were analyzed and processed by using statistic calculation of T-test formula with significance degree 5% and 1%. The formula as follows: To = TO : Test observation MD : Mean of differences; the average score from the differences gained scores between I variable and II variable, which are calculated with the formula; MD = ΣD : Total score between I variable (X variable) and II variable (Y variable). And D is gained with formula; D = X-Y N : Number of cases SDD : The standard deviation from differences between score of X variable and Y variable, which is gained with the formula; SDD = -[ ]2 SEMD : The standard error from mean of differences that is gained with the formula; SEMD = DF : Degree of freedom with formula: N-1 The other data will be done by giving questionnaire to students, and giving the some causes that usually make the boring and ask them to make list based on their opinion. From the questionnaire that had been answered and the list had been arrange it will answer question number one and. Table 3. Conversion Table Total score FSI Level 16 – 25 0+ 26 – 32 1 33 – 42 1+ 43 – 52 2 53 – 63 2+ 63 – 72 3 73 – 82 3+ 83 – 92 4 93 – 99 4+ RESULT AND DISCUSSION Result In this chapter the researcher presented and analyzed the data. Dealing with analyzing the data, the researcher used t-test formula. The data were obtained from the test had been done previously. A. Description of Data After conducting the research, the writer obtained two kinds of data the scores of pre-test and the scores of post-test. And the other one is questionnaire. 1. Pre-test and Post-Test data a. The Pre-Test Scores The data of the pre-test scores can be seen in the table 4 below: No P G V F C T 1 75 53 52 63 52 295 2 76 73 60 68 73 350 3 74 75 68 70 73 360 4 60 85 74 65 86 370 5 72 95 73 77 93 410 6 64 76 73 73 74 360 7 56 48 55 43 45 250 8 56 48 55 43 45 250 9 - - - - - 10 64 76 73 73 74 360 11 77 93 83 78 90 421 12 55 45 60 45 47 252 13 55 56 77 54 54 296 14 53 55 52 53 50 263 15 64 66 62 62 66 320 16 64 66 62 62 66 320 17 72 95 73 77 93 410 18 64 76 73 73 74 360 19 62 74 60 66 68 330 20 63 57 55 60 65 300 21 55 90 65 65 90 365 22 65 84 86 73 82 390 23 63 57 55 60 65 300 24 58 55 55 50 55 273 25 58 55 55 50 55 273 26 65 84 86 73 82 390 27 55 67 55 58 63 298 28 55 67 55 58 63 298 29 64 66 62 62 66 320 After the data is analyzed, it shows that the mean ( x ) is 328 the standard deviation is 15,55 the median is 350 the highest score is 421 and the lowest score is 250. b. The Post-Test Scores The data of the post-test score can be seen in the table 5 below: No P G V F C T 1 82 93 90 80 93 438 2 82 96 80 81 91 430 3 82 92 80 74 93 421 4 74 90 82 74 90 410 5 83 90 82 75 90 420 6 75 90 70 71 90 497 7 82 80 74 72 80 388 8 72 74 72 75 72 365 9 - - - - - 10 82 93 85 72 93 425 11 76 90 82 82 90 420 12 74 90 82 74 90 410 13 80 84 75 75 80 394 14 84 90 83 83 90 430 15 66 70 70 64 72 342 16 74 80 82 74 80 390 17 82 92 80 76 84 416 18 75 90 76 73 90 404 19 75 80 74 71 80 380 20 80 90 82 76 90 418 21 73 90 80 65 90 398 22 82 92 90 84 92 440 23 74 90 82 74 90 410 24 64 72 70 65 72 343 25 72 62 70 55 60 319 26 72 84 80 74 82 392 27 74 70 64 62 70 340 28 74 70 64 62 72 342 29 73 80 65 72 80 370 After the data is analyzed, it shows that the mean ( X ) is 398,28 the standard deviation is 67,684 the median is 394 the highest score is 497 and the lowest score is 319. c. The Comparison of the Test Result The comparison of the test result can be seen in the table 6 below: No Pre Post D D2 1 295 438 -143 20449 2 350 430 -80 6400 3 360 421 -61 3721 4 370 410 -40 1600 5 410 420 -30 900 6 360 497 -137 18769 7 250 388 -138 19044 8 250 365 -115 13225 9 - - - - 10 360 425 -65 4225 11 421 420 1 1 12 252 410 -158 24964 13 296 394 -98 9604 14 263 430 -167 27889 15 320 342 -22 484 16 320 390 -70 4900 17 410 416 6 36 18 360 404 -44 1936 19 330 380 -50 2500 20 300 418 -118 13924 21 365 398 -33 1089 22 390 440 -50 2500 23 300 410 -110 12100 24 273 343 -70 4900 25 273 319 -46 2116 26 390 392 -2 4 27 298 340 -42 1764 28 298 342 -44 1936 29 320 370 -50 2500 N:29 ΣX = 9184 ΣY = 11152 ΣD = -1976 ΣD2 = 203480 Based on the data in table 5, the researcher calculated the result of ΣD = -1976 and ΣD2 = 203480. Then, he tried to find out the standard deviation of differences (SDD) with the formula: SDD = 2 SDD = 2 SDD = SDD = SDD = SDD = 48,72 To find out the mean of differences (MD) between variable X and Y, the researcher used the formula: MD = ∑ MD = MD = 68,13 After gaining the result of SDD = 68.13 the researcher calculated the standard error from mean of differences (SEMD) between variable X and Y: SEMD = SEMD = SEMD = SEMD = SEMD = 9,22 The last calculation is determining the result of t observation (to) of the test with formula: To = To = To = 7,389 The result 7,389 indicated that there was a difference of degree as much as 7,389. Regardless the minus, it doesn.t indicate negative score. Then, to complete the result of the research, the writer finds out the degree of freedom (df) with the formula: df = N - 1 = 29-1 = 28 df = 28 (see table of .t. value at the degree of significance of 5% and 1%) At the degree of significance 5% = 2,045 At the degree of significance 1% = 2,756 The result is 2,045 < 7,389 > 2,756 The result of analyzing the data by using the above formula shows that the coefficient is 7,389. It means that there is a significance improvement after the informational gap activity is used to teach speaking. B. Discussion After doing the research and analyzing the data. Let me analyze in other way as below : Table 7. The Result of Pre-test and Post-test Group Pre-test Post-test Observed-t Pre-Test and Post-test Single Group 328 398.28 7,389 From the table above, it showed the mean score of pre-test is 328 and the mean score of post-test is 398.28 It means that there was really significant difference and improvement of the score between them. Based on the result of the data analysis, it is proven that the students. Score of speaking taught by using Informational Gap Activity is better. It means that the use of information gap activity in teaching speaking is quite effective. Another reason based on the students. Responses are because most students find that information gap activity is enjoyable. This reason leads to better attention in learning and stimulate them to participate in information gap activity. But the problem that they faced mostly is lack of confidence and lack of vocabulary. In the early stages of the Informational Gap Activity the students were uncomfortable and uncertain. This led to initial lapses of silence. But soon they began helping one another to decide who should speak. Towards the end, their shyness left them and they began prompting each other with ideas. It can be told that “Informational Gap Activity” is the one of methods that can be used to teach and improve unmotivated students’ speaking ability. The prove is that there is improvement of students’ speaking score after treated by using Informational Gap Activity and that is really good effect of Informational Gap Activity. CONCLUSION AND SUGGESTION Conclusion Based on the research, the writer concludes that: From the result of the analysis of the research, it is proven that the students. Score of speaking taught by using Informational Gap Activity is better than before. And based on the result has answered by the research question, shows that using information activity in teaching speaking is quite effective. The use of information activity makes teaching learning and speaking activity more enjoyable and interesting. Simply that the technique the teacher use is quite attracting them and helps the shy students by providing a mask, where students with difficulty in conversation are liberated. In addition, it is fun and most students will agree that enjoyment leads to better learning. Here, the students have to practice speaking and find the answer themselves of course by asking friend. It will make them confident to speak. In information activity, the world of the classroom is broadened to include the outside world. This offers a much wider range of language opportunities. So, the students can be anyone and in any situation they wish. The use of information activity makes the class more active and alive. Students are willing to participate without any forces from the teacher. The use of information activity makes the students more motivated in learning and easier to grasp the lesson. Problems that the students faced mostly in Informational Gap Activity are lack of confidence and lack of vocabulary. B. Suggestion The success in teaching doesn.t depend on the lesson program only, but more important is how the teacher presents the lesson and uses various techniques to manage the class more lively and enjoyable. Regarding to the teaching speaking by using Informational Gap Activity, the writer gives some suggestion for the teacher and students as follow: For the teacher: The teacher should choose the materials that are appropriate and not too difficult for the students. Before assigning the information activity to the students, the teacher should make sure that the students have fully understood and have the information they need. The teacher should keep control the student activities. The teacher should present the language in an enjoyable, relaxed and understandable way. For the students: The students are hoped not to be shy in acting out their role. The students are hoped to be active and creative in enriching their vocabularies. The students are hoped to use English when they practice Informational Gap Activity although it is hard for them. The students should take part REFERENCES Sasson, Dorit. 2008. Information Gap Activities: Working in Groups or Pairs during Cooperative Learning Lessons. Available on http://lesson-plan-help.suite101.com/article.cfm/ learning games Bartz, HE. 1976. Basic Statistical in Education and Behavioral Sciences. Burgess Publishing Company. Mc Millan, J. H. 1992. Education Research Fundamentals for the customer. New York: Harper Collin Publisher Beard, P. R. (2008, November Thursday 13). What is the Role of the Teacher Today? Teacher’s quality. Brewster, C. &. (October 22, 2007). Increasing Student engagement and motivation. Donald ary, l. c. (2006). Introduction to research in education. Dornyei, Z. (1994). Motivation and Motivating in the Foreign Language Classroom.The Modern Language Journal, Vol. 78, No. 3, pp. 273-284 . Hicks, C., & Glasgow, N. &. ((2005)). what successful mentors do. Leech, B. L. (2003). Techniques for Semi-structured Interviews. Political Science and Politics, Vol. 35, No. 4. Defrioka, A (2009). Improving Students’ Interaction in Speaking Class Through Information GAP Activities, Vol.3 No.2 33-45 Richards, k. (2003). Qualitative Inquiry in tesol. Qualitative Inquiry . Schmidt, B. &. (1996). Foreign Language Motivation: Internal and external connections. Path Ways to the New Century. Fitriah, M. 2010. Improving Speaking Ability of Descriptive Text Use “Three-Step Interview for Eight Graders of SMPN 26 Surabaya”. Brown, H. Douglas. 1994. Principal of Language Learning and Teaching. Third Edition. New Jersey: Prentice Hall Tudor, Ian. 2001. The Dynamic of the Language Classroom. UK: Cambridge University